Student dropout in Colombia and the engineering programs of the Uptc campus Sogamoso - Higuera-Martinez, Oscar Ivan (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
This paper presents an analysis of student dropout in Colombia. Initially in the programs areas that Uptc Sogamoso has and finally focusing on the Engineering programs in the campus, where the data reported by SPADIES (System for the Prevention of Dropout in Institutions of Higher Education) are reviewed, and a description is made of the results reported and the some variables that influence the dropout in the Uptc Sogamoso.